As ações coletivas como mecanismo de controle social no esporte - Toledo, Victor Miranda de (2022)
With the objective of indicating that Class Actions are the most effective means to promote social pacification in sports matters, the present study addresses the necessary structure to demonstrate the hypothesis. Sports Law, as it is self-regulating and autopoietic, demonstrates conditions to resolve in its microsystem the issues inherent to its regular activity, which is constitutionally guaranteed. However, in the present study, there is a theoretical demonstration and also through practical cases, that once urged to solve the intrinsic issues of its microsystem that eventually not overcome through self-resolution, Sports Law is assured the search for jurisdiction before the Common Justice, given that depending on the characteristics of their demands, the application of an erga omnes solution becomes inexorably more effective. It is demonstrated, therefore, by discussing the interrelationship of the Sports Law microsystem with other microsystems inserted in the Legal macrosystem, which using procedural instruments of a diffuse, collective or homogeneous individual nature, such as the Public Civil Action or even the Popular Action, for example, the search for the protected good effectively achieves its objective as the most adequate solution, in a broad and unrestricted way